SCHOOL ORIENTATIONS IN THE POST-PANDEMIC ERA - Florentin Remus MOGONEA; Marian PĂDURE (Universitaria Publishing House, Craiova, 2024)
March 11, 2020 was the day when in Romania the pandemic moved school classes online. Nobody had the slightest idea that we were facing an entirely new situation. An invisible enemy (Covid-19) started to spread fear, changed rules and behaviors. Most of us gave up natural gestures, changed our way of working, vacations were different or didn't take place at all, in short, we adapted to a different lifestyle. The school and the children were struck by the pandemic in a very particular way. Schools closed and no one knew what was coming, because no one was prepared for something like that. The consequences were unsuspected, for the students, parents and teachers alike: they all found themselves in an unpredicted situation. The shock was strong. The Romanian education system had to adapt along the way, to enter, for the beginning, in the virtual, online or hybrid meeting. The communication difficulties, at least at the beginning, were very high. Even now, the shortages of the pandemic period are being felt. But, despite all these, the school had to go forward, to function. The directions of action were and are multiple, involving various scenarios. Although even today this enemy has not disappeared, teachers, parents, students and education specialists continue to find plausible scenarios for the good functioning of the school and society.